Post-calibration and quality management of weigh-in-motion traffic data - De Wet, Dirk Pieter Gerhardus (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Process Engineering))--University of Stellenbosch, 2010.